Concepção de leitura na formação continuada: implicações no processo de organização da prática pedagógica - Zago, Lauciane Piovesan (2013)
When we understand that education is a practical intervention in social reality, but that alone is not enough to make organizational changes in society, we must understand it as a multidimensional phenomenon, composed of a complex set of perspectives and approaches. It is interwoven with the educational policy aimed primarily at improving the Index Basic Education Development (IDEB), the teaching practice in their daily lives, pursue, in essence, two offices of teaching: fulfill its function of teaching everyone, with quality, scientific knowledge developed and accumulated by mankind, and ensure that their students improve their performance and their school, therefore, in large-scale assessments. This research, linked to the Centre of Education (UNIOESTE / INEP / CNPq) and the research project "Continuing education for teachers of basic education in the early years: actions for municipalities with low literacy IDEB the western Paraná University of West of Paraná, which includes the provision of training for teachers can materialize a valuable and effective in improving the quality of education in the country. Based on these assumptions, we question our research with the following questions: Continuing education can affect the pedagogical action? In what way? And: What are the implications of (s) design (s) reading teachers in the pedagogical actions? Given these interpellations and subsidized by the theories of reading, from the theoretical principles of Enunciation Linguistics, Applied Linguistics and socio-historical perspective of teaching and learning through the interactive conception of language, we aim to cast an eye on the process of formation Continuing developed in the city of Diamond South in 2011 and, inset, the concept of reading the participating teachers. This research aims to understand how continuing education interfere in the actions of teachers teaching reading 5th grade of elementary school I. Registered under the aegis of Applied Linguistics, contend that work on the qualitative approach, based on ethnographic research, since the scenario enters the classroom. From the data generated, it was possible sometimes evident in teachers' discourse marks an interactive conception of reading / language, however, certify that the work in LP is still strongly marked by a structuralist view of language.